Emotions and Reactions to the Confinement by COVID-19 of Children and Adolescents With High Abilities and Community Samples: A Mixed Methods Research Study - Valadez, María de los Dolores; López-Aymes, Gabriela; Ruvalcaba, Norma Alicia; Flores, Francisco; Ortíz, Grecia; Rodríguez, Celia; Borges, África (Frontiers in Psychology, 2020)
The goal of this research is to know and compare the emotions and reactions to the confinement due to the COVID-19 of children and adolescents with high abilities and community samples. This is a mixed study with an exploratory reach, descriptive and correlational combining survey and qualitative methodologies, that allowed to know the emotions and reactions to the confinement of the COVID-19 of children and adolescents between 5 and 14 years old with high abilities and community samples. An online poll was designed with 46 questions, grouped in 3 sections: 1) General Data, 2) Reactions to the health contingency of the COVID-19, 3) Positive and negative emotions. To this last section, was included the Oros’ positive emotions questionnaire (2014) and the scales of negative affect of the PANAS Schedule positive and negative affect on children and adolescents between 8 and 14 years old (Sandin, 2003). Data was collected online with a convenience sample. Quantitative data was analyzed with SPSS statistical program and qualitative data with Alceste software. Among the main findings is that there are no significant differences between the groups by ability on reactions and emotions; however, there are differences between age groups and sex. It is discussed the implications for the educational intervention in the face of situations like the one caused by the current pandemic.